HUBUNGAN PENGETAHUAN PENGOMPOSAN SAMPAH MANDIRI DENGAN JUMLAH SAMPAH RUMAH TANGGA DI KECAMATAN PASAR KLIWON - Prasetyo, Agung; Mahananto, Mahananto; Setiawan, Anggit Tory (Universitas Islam Kadiri, 2024)
Household waste is a major problem in Semanggi Mojo, Surakarta. This densely populated region faces challenges in waste processing, but composting can reduce them. This research aims to measure the level of knowledge of the community in Semanggi Mojo, Pasar Kliwon District regarding the practice of independent waste composting and the relationship between this knowledge and the amount of household waste in the area. This research was conducted using a survey method, the research location was deliberately determined in Semanggi Mojo, Pasar Kliwon District, Surakarta City. The total research sample was 51 respondents. Sample determination was carried out using a proportional random method. Data collection was carried out in August-September 2023. The results showed that X2 (Skills) and X3 (Economy) had a relationship with Y (Amount of Waste), while other variables were not related. Public awareness of waste composting is quite good, with skills reflecting the ability to manage waste and economic problems related to management. Social and cultural factors also influence household waste management.